Echoes of the Sudan war and its social and economic repercussions on the city of Port Sudan (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study dealt with the repercussions of the Sudan war and its social and economic repercussions on the city of Port Sudan, as the study aimed to reflect the suffering of the displaced, know the real numbers of them, shed light on their problems and propose appropriate solutions, as indicated by the impact of non-governmental organizations in providing them with assistance. The problem of the study was the weakness of the infrastructure, especially water and electricity services, which the state already suffers from, which negatively affects the suffering of the displaced. The study followed the descriptive analytical approach and the qualitative approach in social research. The study reached a number of results, the most important of which was that the displaced in the state are estimated at 239,000 displaced people residing in 80 shelter centers and 21,400 families residing outside the shelter centers. The city of Port Sudan contained 95% of the shelter centers. The most important problems of the displaced were the loss of sources of income, overcrowding in the shelter centers, the lack of adequate food, the inappropriateness of tents for the city's weather, and the instability of electricity. The King Salman Relief Center was one of the largest supporters of the displaced in addition to the Qatar Charity. The study also made some recommendations, the most important of which was the need to establish desalination plants for water, electricity or solar power generators, in addition to providing health and psychological care and rehabilitating toilets to take into account people with special needs.
Keywords: Sudan War; Social Repercussions; Economic Repercussions; City of Port Sudan